2019
DOI: 10.5607/en.2019.28.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Identifies Alterations of Amino Acid Metabolome Signatures in the Postmortem Brain of Alzheimer's Disease

Abstract: Despite significant advances in neuroscience research over the past several decades, the exact cause of AD has not yet fully understood. The metabolic hypothesis as well as the amyloid and tau hypotheses have been proposed to be associated with AD pathogenesis. In order to identify metabolome signatures from the postmortem brains of sporadic AD patients and control subjects, we performed ultra performance liquid chromatography coupled with linear ion trap-Orbitrap mass spectrometer (UPLC-LTQ-Orbitrap-MS). Not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…Myo‐inositol is generally considered to be a marker of astroglial activity (Harris et al., 2015). Several studies have shown increased levels of this metabolite (González‐Domínguez, García‐Barrera, Vitorica, et al, 2014; Kim et al., 2019; Woo et al., 2010), except one which was consistent with our finding and was downregulated (Lalande et al., 2014). Both SAH and SMC are Hcy derivatives.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Myo‐inositol is generally considered to be a marker of astroglial activity (Harris et al., 2015). Several studies have shown increased levels of this metabolite (González‐Domínguez, García‐Barrera, Vitorica, et al, 2014; Kim et al., 2019; Woo et al., 2010), except one which was consistent with our finding and was downregulated (Lalande et al., 2014). Both SAH and SMC are Hcy derivatives.…”
Section: Discussionsupporting
confidence: 92%
“…Clearly, the main pathways and related mechanisms associated with differential metabolites in 6M group are consistent with 2M group. Indeed, they have previously been reported to be associated with AD (González‐Domínguez et al., 2017; González‐Domínguez, García‐Barrera, Vitorica,, et al., 2014; Griffin & Bradshaw, 2017; Kim et al., 2019; Kori et al., 2016; Toledo et al., 2017; Varma et al., 2018). However, the 6M group produced more differential metabolites than the 2M group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar analytical approach was employed to predict the progression of AD along four diagnostic groups, namely healthy control subjects, stable MCI patients, MCI subjects who developed AD after a 2-year follow-up, and AD patients, which indicated significant alterations in the CSF levels of some amino acids and taurine-related metabolites [ 52 ]. Comparable findings have been obtained from brain metabolomics profiling, thus suggesting that modulating the metabolism of amino acids could be a possible therapeutic approach against AD [ 53 ]. Additionally, in the brain, Paglia et al found profound cortical perturbations in the metabolism of glycerophospholipids and six central metabolic pathways, of which a significant impairment of the mitochondrial aspartate metabolism was noteworthy [ 54 ].…”
Section: Alzheimer’s Disease and Hilic-ms-based Metabolomicsmentioning
confidence: 96%
“…D-Glutamate (Glu) is not present in brain although it is present in blood (Weatherly et al, 2017) and inclusion of the D-glutamine (Gln) and D-Glu metabolism pathway in brain is not correct. (Kim et al, 2019).…”
Section: Interpre Tati On Of Sof T Ware-g Ener Ated Re Sultsmentioning
confidence: 99%